Modeling of oil revenues impact to the dynamics of main macroeconomic indicators of Кazakhstan (Journal of Economic Research & Business Administration, 2015)
This paper presents a model of the dynamic stochastic general equilibrium for the economy of Kazakhstan. Parameters of the model were evaluated. The model includes oil production sector , which plays an important role in the economy, and provides a significant share of revenues to the state budget. Response functions of macroeconomic indicators to internal and external shocks to the economy of Kazakhstan were analyzed. Internal shocks are a shock of performance in the final goods sector, a productivity shock in the oil sector, a labor preference shock, a shock of monetary policy, external shocks are an oil price shock, an oil demand abroad shock and a shock of a production abroad. Accounting of indicators responses to shocks will allow to predict the consequences of decisions in the economy, as well as external influences to the economy.
Keywords: economics; modeling; general equilibrium; model of dynamic; stochastic model; monetary policy; the new Keynesian model